Assessing climate change impacts and adaptation strategies for smallholder agricultural systems in Uganda - Bagamba, F.; Bashaasha, B.; Claessens, Lieven; Antle, John M. (2012)
The debate on whether climate change will impact on peoples’ livelihoods and, hence, the need to act is essentially over and has instead shifted to the development of strategies needed by different regions and countries to adapt to climate change effects. However, there is still scanty information necessary to ably address climate change related issues. There is a considerable knowledge gap with respect to climate change impact, vulnerability and adaptation to increased climate variability and change. In this paper, using the trade off analysis model, the impact of climate change on peoples’ livelihoods and possible adaptation strategies to increase the resilience and sustainability of agricultural systems in three regions of Uganda (central, Masaka and southwest) are analysed. The results show that 70-97% of households will be adversely affected by climate change in Uganda. The southwest will be most affected due to smaller farm sizes and limited livelihood alternatives. There will be no positive gains from encroaching on swamps, which is one of the reported adaptation strategies to climate related stresses. Improving productivity of important crops (bananas for southwest, and sweet potatoes and bananas for central region), in addition to adoption of grade cattle will likely be a better adaptation strategy for climate change.